2021
DOI: 10.3390/w13141964
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Transfer in Two-Stage Activated Sludge Wastewater Treatment Plants

Abstract: Aeration is an energy-intensive process of aerobic biological treatment in wastewater treatment plants (WWTP). Two-stage processes enable energy-efficient operation, but oxygen transfer has not been studied in depth before. In this study, α-factors were determined with long-term ex situ steady-state off-gas measurements in pilot-scale test reactors (5.8 m height, 8.3 m3) coupled to full-scale activated sludge basins. A two-stage WWTP with more than 1 Mio population equivalent was studied over 13 months includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…A previous study has shown that the effect of fouling during long-term off-gas measurements could be kept low when applying this maintenance (Schwarz et al 2021). Here, clean water tests repeated over a period of 13 months revealed a decrease of SOTR of 2 to 6% depending on airflow rate and a dynamic wet pressure increase of about 1 kPa.…”
Section: Fouling Factor -F ( −)mentioning
confidence: 64%
“…A previous study has shown that the effect of fouling during long-term off-gas measurements could be kept low when applying this maintenance (Schwarz et al 2021). Here, clean water tests repeated over a period of 13 months revealed a decrease of SOTR of 2 to 6% depending on airflow rate and a dynamic wet pressure increase of about 1 kPa.…”
Section: Fouling Factor -F ( −)mentioning
confidence: 64%
“…In the present case, the high α values could be explained by the fact that the industrial wastewater is permanently slightly polluted. Surfactants and other possible oxygen-transfer-inhibiting constitutions were not explicitly measured, but elevated concentrations of such substances are usually accompanied by an increased organic concentration in the influent [8,27,30]. An increased concentration of such substances in the influent is, therefore, most unlikely.…”
Section: α Valuementioning
confidence: 99%
“…), the given equations for calculating fS (see Section 3.2.) for the corresponding membrane design and a fixed α in the standard oxygen transfer rate in the process water (SOTRPW; kg/h), standardized at DO = 0 mg/L, atmospheric pressure = 101.3 kPa and T = 20 °C: A possible explanation is that the salt shock caused the microorganisms to produce oxygen-transfer-inhibiting substances [6,8,29,30]. Since the influent was stopped during the salt dosage, these substances accumulated in the system (i.e., reactor B1 and B2), thereby enhancing the effect.…”
Section: Performance Comparison Of Both Diffuser Membrane Designsmentioning
confidence: 99%
“…Studies on the computational fluid dynamics (CFD) model have revealed that the OTR is directly related to the hydrodynamics inside bioreactors [20,21]. In particular, it has been shown that higher turbulence intensity leads to an increase in the oxygen mass transfer coefficient, and hence oxygen uptake [22][23][24].…”
Section: Introductionmentioning
confidence: 99%